The Increased Neglect of Children Between 7-10 Years of Age in Kigado-Kayanga Village, Kiruhura District - Kyarikunda, Lilliane B (Kampala : Uganda Christian University, 2010)
Descriptive Cataloguing Dissertation (MHRME) Uganda Christian University Mukono.
Includes bibliographical references and appendix
Keywords: Child neglect